2018
DOI: 10.1371/journal.pone.0209651
|View full text |Cite
|
Sign up to set email alerts
|

English verb regularization in books and tweets

Abstract: The English language has evolved dramatically throughout its lifespan, to the extent that a modern speaker of Old English would be incomprehensible without translation. One concrete indicator of this process is the movement from irregular to regular (-ed) forms for the past tense of verbs. In this study we quantify the extent of verb regularization using two vastly disparate datasets: (1) Six years of published books scanned by Google (2003–2008), and (2) A decade of social media messages posted to Twitter (20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Their main focus is the (ir)regularization of past-tense verbs (e.g. the change from irregular snuck to regular sneaked), a topic that has been of some interest (Lieberman et al 2007;Cuskley et al 2014;Gray et al 2018). They also investigate the change in periphrastic do (say not that!…”
Section: Introductionmentioning
confidence: 99%
“…Their main focus is the (ir)regularization of past-tense verbs (e.g. the change from irregular snuck to regular sneaked), a topic that has been of some interest (Lieberman et al 2007;Cuskley et al 2014;Gray et al 2018). They also investigate the change in periphrastic do (say not that!…”
Section: Introductionmentioning
confidence: 99%
“…These tools may be particularly useful for researchers in philosophy, English, and other disciplines who are interested in quantifying aspects of discourse. Researchers in the digital humanities have recently made a number of interesting advances (8,9,13,45,46), and with the right tools, hopefully scholars can begin to quantify features of culture only dreamed about previously.…”
Section: Discussionmentioning
confidence: 99%
“…Spring Forward is defined as the instantaneous clock adjustment from 2 a.m. to 3 a.m. on the second Sunday of March each year. We included tweets in the study if the user who created the tweet reported living in the U.S. in their bio, or if the tweet was geo-tagged to a GPS coordinate within the U.S. [44]. With these conditions, we ended up selecting approximately 7% of the messages in the Decahose random sample for analysis [45].…”
Section: Datamentioning
confidence: 99%